Starategi Guru Sekolah Minggu Untuk Mempertahankan Karakter Iman Anak Sekolah Minggu Masa Pandemi Covid 19 - Spenerhard Makahinsade (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2021)
This paper is a theological analysis of the situation during the Covid 19 pandemic where the church is not ready to serve the congregation, let alone to hold a Sunday School Children's worship meeting which is held two or three times a week. This will reduce the quality and quality of faith that is loose in the growth and development of faith in Sunday school children. So that the author wants to conduct scientific research during the Covid 19 pandemic by examining